2006
DOI: 10.1007/s00595-005-3181-6
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-DTPA-Galactosyl-Human-Serum-Albumin Liver Scintigraphy for Evaluating Hepatic Functional Reserve Before Hepatectomy in a Patient with Indocyanine Green Excretory Defect: Report of a Case

Abstract: A 78-year-old woman with indocyanine green (ICG) excretory defect underwent left hepatectomy for cystadenocarcinoma. The retention rate of ICG at 15 min (ICGR(15)) was high, at 79.3%, despite all other liver function tests showing normal values. Conversely, 99mTc-DTPA-galactosyl-human-serum-albumin (GSA) liver scintigraphy showed a reduced accumulation of GSA in the left lateral lobe, the hepatic uptake ratio of the GSA scintigraphy was 0.96, and the arterial ketone body ratio was 1.67. Based on these results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Therefore, preoperative assessment of the function of the remnant liver is essential when planning major hepatectomy. Several methods have been tested for their ability to predict postoperative hepatic function2–6, including the Child–Pugh score2, volumetric measurement of the liver remnant3, plasma clearance rate of indocyanine green (ICGK)4 and 99m Tc‐labelled galactosyl human serum albumin scintigraphy5, 6. There remains controversy concerning which method is the simplest and most reliable in predicting postoperative morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preoperative assessment of the function of the remnant liver is essential when planning major hepatectomy. Several methods have been tested for their ability to predict postoperative hepatic function2–6, including the Child–Pugh score2, volumetric measurement of the liver remnant3, plasma clearance rate of indocyanine green (ICGK)4 and 99m Tc‐labelled galactosyl human serum albumin scintigraphy5, 6. There remains controversy concerning which method is the simplest and most reliable in predicting postoperative morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…One important factor in ensuring the safety of the patients is the appropriate determination of the preoperative resected liver volume by the precise evaluation of the hepatic functional reserve [6], and thus an accurate assessment of the hepatic functional reserve is essential before performing a hepatectomy. Hematobiochemical examinations, which include the measurement of T-Bil, Alb, and PT, and HPT and the ICG test, are usually used as preoperative hepatic functional reserve tests, but even the ICG test lacks accuracy because patients may have an ICG excretory defect [7]. Therefore, GSA scintigraphy has been recently accepted as the most accurate and non-invasive modality to assess the preoperative hepatic functional reserve for patients at many medical facilities [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of hepatectomy in patients with an ICG excretory defect have been reported [1, 3, 13, 14], and hepatectomy could be performed safely within the limits of hepatic functional reserve. It is certain that ICG excretory defect itself does not affect hepatic functional reserve from these results, but human OATP1B1 and OATP1B3 mediate the uptake of many drugs by the liver, and even polymorphisms of OATP1B1 and OATP1B3 that are associated with reduced activity can result in life-threatening drug toxicities [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the selective impairment of plasma ICG clearance with normal liver histology. The pathophysiology involves selective loss of active transporters for ICG in the hepatic cell membrane [3]. Recently, it has been reported that organic anion transporting polypeptides (OATPs; encoded by SLCOs) and Na + -taurocholate cotransporting polypeptides (NTCPs; encoded by SLC10A1), which are present in the basolateral membrane of human hepatocytes, are important transporters for the uptake of substances and xenobiotics, and are positively correlated with the transporters for ICG [4].…”
Section: Introductionmentioning
confidence: 99%